Rethinking the impact of the protonable amine density on cationic polymers for gene delivery: A comparative study of partially hydrolyzed poly(2-ethyl-2-oxazoline)s and linear poly(ethylene imine)s - Bauer, Marius; Tauhardt, Lutz; Lambermont-Thijs, Hanneke M. L.; Kempe, Kristian; Hoogenboom, Richard; Schubert, Ulrich S.; Fischer, Dagmar (European Journal of Pharmaceutics and Biopharmaceutics, 2018)
To gain a more profound insight into the impact of the number and the density of protonable amines on the performance of polycations as non-viral vectors, a series of linear poly(ethylene imine)s (LPEIs) with different numbers of ethylene imine (EI) units was compared to partially hydrolyzed (21 to 86%, 20 kDa) poly(2-ethyl-2-oxazoline)s (PHPEtOxs) with a corresponding number of EI units but with varying densities. PHPEtOx polyplexes demonstrated lower transfection efficiencies than the corresponding LPEIs although having the same number of EI units as LPEI, exhibiting smaller or comparable polyplex diameters, similar zeta potentials, and similar or even preferred cyto- and hemocompatibility profiles. The lower efficiency was found to be related to a lower DNA binding capacity and less efficient protection of plasmid DNA against enzymatic degradation. The direct comparison of both types of polymers revealed that the density of charges within the polymer backbone seems to be more important than the total number of EI units. In conclusion, the reduction of the EI density to produce more biocompatible polyplexes must be critically examined, since the presence of high numbers of EI next to each other seems to have a dramatically higher impact on the transfection efficiency than on the in vitro toxicity.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Gene delivery; Non-viral vector; Poly(2-ethyl-2-oxazoline); Poly(ethylene imine); Polymer; Transfection